2019
DOI: 10.1371/journal.pone.0207675
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial regulation of macrophage bacterial recognition receptors in COPD are differentially modified by budesonide and fluticasone propionate

Abstract: RationalePatients with COPD have an increased risk for community-acquired pneumonia, which is further increased by inhaled corticosteroids.ObjectiveTo assess effects of the corticosteroids, budesonide and fluticasone propionate, on macrophage bacterial responses in COPD.MethodsMonocyte-derived macrophages (MDMs) generated from blood monocytes from 10 non-smoker controls (NoS), 20 smokers without COPD (Sm), and 40 subjects with moderate to severe COPD (21 ex-smokers (COPD-ES) and 19 current smokers (COPD-S)) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
4
11
0
Order By: Relevance
“…Due to its greater lipophilicity and tenfold higher immunosuppressant potency, the prolonged residency time of FP in the airway epithelial lining fluid compared with budesonide may result in an increased duration of local immunosuppression and impaired pathogen clearance from the airways [14, 75, 154]. Additionally, very recent work has demonstrated a differential response to budesonide compared with FP in blood-derived macrophages in smokers and ex-smokers with COPD [155]. Budesonide counteracted reductions in bacterial recognition receptors on monocyte-derived macrophages by both non-typeable Haemophilus influenzae and Streptococcus pneumoniae , whereas FP only counteracted some of the reductions by S. pneumoniae.…”
Section: Safetymentioning
confidence: 99%
“…Due to its greater lipophilicity and tenfold higher immunosuppressant potency, the prolonged residency time of FP in the airway epithelial lining fluid compared with budesonide may result in an increased duration of local immunosuppression and impaired pathogen clearance from the airways [14, 75, 154]. Additionally, very recent work has demonstrated a differential response to budesonide compared with FP in blood-derived macrophages in smokers and ex-smokers with COPD [155]. Budesonide counteracted reductions in bacterial recognition receptors on monocyte-derived macrophages by both non-typeable Haemophilus influenzae and Streptococcus pneumoniae , whereas FP only counteracted some of the reductions by S. pneumoniae.…”
Section: Safetymentioning
confidence: 99%
“…Preliminary results show that budesonide prevented receptor reductions induced by both S. pneumoniae and non-typeable H. influenzae , while fluticasone propionate affected only reductions induced by S. pneumoniae . 57 The authors of these reports concluded that differential regulation of immune defense genes in human bronchial epithelial cells 56 and bacterial pathogen recognition receptors on macrophages 57 may help to explain the difference between fluticasone propionate and budesonide with respect to the risk of pneumonia. Mechanisms responsible for these differences in gene regulation are not clear; however, recently, it was shown that different corticosteroids express a unique gene “fingerprint”, 58 which could explain some differences between effects of fluticasone propionate and budesonide.…”
Section: Local Bronchial Immunity – the Link To The Development Of Pnmentioning
confidence: 99%
“…In COPD, alveolar macrophages and macrophages derived from blood monocytes have an impaired ability to phagocytose and kill respiratory pathogens, which may contribute to the increased bacterial colonization in COPD. 59 61 In the study described above, 57 where bacterial recognition receptors in macrophages derived from blood monocytes of COPD subjects were differently affected by budesonide and fluticasone propionate, phagocytosis of bacteria was not studied. However, in the study by Taylor et al, phagocytosis of S. pneumoniae and H. influenzae by macrophages derived from blood monocytes from COPD patients was increased when cells were treated with budesonide.…”
Section: Local Bronchial Immunity – the Link To The Development Of Pnmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinical studies have reported that budesonide has lesser effects on pneumonia risk than FP, 1 , 2 with in vitro studies suggesting that this may be related to differential effects on bacterial adhesion 9 or receptor expression. 10 We observed no difference in the ability of FP and budesonide to impair cathelicidin and increase bacterial burden. In contrast to these other studies, which have solely used in vitro experiments, we report equivalent effects of FP and budesonide both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 54%